Social Inclusion Through the Digitalization of Civil Registration Services for Vulnerable Communities in Manado City (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The digital transformation of civil registration and vital statistics services is crucial for achieving efficient, transparent, and inclusive public governance. However, digital-based services have not yet provided equal access for all social groups, especially vulnerable populations such as coastal communities, persons with disabilities, and low-income families. This creates challenges in achieving social equity through the digitalization of public services. This study aims to examine the implementation of digital civil registration services in Manado City and evaluate their role in promoting social inclusion for vulnerable communities. A qualitative descriptive method with a case study approach was used at the Department of Population and Civil Registration (Dukcapil) of Manado City. Data were collected through in-depth interviews, field observations, and document analysis, analyzed using Miles and Huberman’s interactive model, which includes data reduction, display, and conclusion drawing. The findings indicate that while the digitalization of services through the Centralized Population Administration Information Sistem (SIAK Terpusat) and Digital Population Identity (IKD) has improved administrative efficiency, it has not yet fully achieved inclusivity. Key challenges include limited digital literacy, inadequate infrastructure, and insufficient service personnel capacity. In conclusion, digitalization in Manado City has the potential to strengthen social inclusion, provided there are improvements in digital literacy, human resource capacity, and collaboration between the government, communities, and the private sector. The study recommends integrating outreach initiatives with a citizen-based digital service framework to ensure equitable access for all, including vulnerable groups.